Professor Evgueni A. Haroutunian - Council, Editorial (Mathematical Problems of Computer Science, 2021)
Professor Evgueni A. Haroutunian, a recognized scientist and respected teacher, Chief Researcher of the Institute for Informatics and Automation Problems of the NAS of RA, Founder of the Scientific School of Information Theory in Armenia, was the Deputy Editor of Transactions of IIAP NAS RA “Mathematical Problems of Computer Science” for many years.